2021
DOI: 10.1186/s10020-021-00385-1
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MAPKAPK5-AS1 promoted lipopolysaccharide-induced inflammatory damage in the myocardium by sponging microRNA-124-3p/E2F3

Abstract: Background Myocardial dysfunction caused by sepsis (SIMD) leads to high mortality in critically ill patients. We investigated the function and mechanism of long non-coding RNA MAPKAPK5-AS1 (lncRNA MAPKAPK-AS1) on lipopolysaccharide (LPS)-induced inflammation response in vivo and in vitro. Method Male SD rats were utilized for in vivo experiments. Rat cardiomyocytes (H9C2) were employed for in vitro experiments. Western blotting was employed to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Myocardial infarction is defined as cardiomyocyte cell death and its progression involves the regulation of noncoding RNAs such as long noncoding RNAs, miRNAs and circRNAs 19–22 . Dill et al have reported that the imprinted Dlk1‐Dio3 genomic region that contains a noncoding RNA cluster and regulates cardiac homeostasis has the potential as a therapeutic target for CVDs 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial infarction is defined as cardiomyocyte cell death and its progression involves the regulation of noncoding RNAs such as long noncoding RNAs, miRNAs and circRNAs 19–22 . Dill et al have reported that the imprinted Dlk1‐Dio3 genomic region that contains a noncoding RNA cluster and regulates cardiac homeostasis has the potential as a therapeutic target for CVDs 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial infarction is defined as cardiomyocyte cell death and its progression involves the regulation of noncoding RNAs such as long noncoding RNAs, miRNAs and circRNAs. [19][20][21][22] Dill et al have reported that the imprinted Dlk1-Dio3 genomic region that contains a noncoding RNA cluster and regulates cardiac homeostasis has the potential as a therapeutic target for CVDs. 23 Convincing evidence has indicated the contribution of circRNAs to cardiac inflammation, cardiac fibrosis, cardiac regeneration, autophagy, apoptosis, and oxidative stress signaling during myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Grouping: The mice were grouped randomly as follows (N = 12): (1) control group: injected intraperitoneally with 10 mg/kg normal saline at one time, with other treatments the same as the LPS group; (2) LPS group; (3) LPS + oe-LncSICRNT1 group: immediately injected with oe-LncSICRNT1 adeno-associated virus plasmids (19 × 10 7 TU/per mouse) via tail veins after modeling [ 40 ]; (4) LPS + oe-negative control (NC) group: immediately injected with an equivalent amount of oe-NC plasmids via tail veins after modeling; (5) LPS + XYT-L, M, and H group (the mice were intragastrically administered with low-, medium-, and high-dose XYT on day 2 after modeling); (6) LPS + digoxin group (positive drug control group); (7) LPS + XYT-M + si-LncSICRNT1 group: immediately injected with si-LncSICRNT1 plasmids (19 × 10 7 TU/per mouse) via tail veins and treated with medium-dose XYT suspension 2 days later after modeling; (8) LPS + XYT-M + si-NC group: immediately injected with equivalent amounts of si-NC plasmids and treated with medium-dose XYT suspension on the second day after modeling. All plasmids were provided by GenePharma (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The lncRNA-mediated ceRNA networks regulate cardiovascular toxicity in sepsis as shown in Tables 1 , 2 (Ref. [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]).…”
Section: Competing Endogenous Rnas In the Regulation Of Scvdsmentioning
confidence: 99%
“…Both in vivo and in vitro experiments indicated that NEAT1 was an upstream regulator of NF- B and a ceRNA of miR-144-3p . The lncRNA MAP kinase-activated protein kinase 5 antisense gene protein 1 ( MAPKAPK5-AS1 ) was significantly upregulated in LPS-treated SD rats and H9C2 cells [ 39 ]. Knockdown of MAPKAPK5-AS1 inhibited inflammatory response by targeting miR-124-3p to downregulate the expression of E2F3.…”
Section: Competing Endogenous Rna Network In Scvdsmentioning
confidence: 99%